2020
DOI: 10.1111/jnc.15222
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex miR‐874‐3p prevents lipopolysaccharide‐induced depression‐like behavior through inhibition of indoleamine 2,3‐dioxygenase 1 expression in mice

Abstract: Indoleamine 2,3‐dioxygenase 1 (IDO1) is the first rate‐limiting enzyme that metabolizes tryptophan to the kynurenine pathway. Its activity is highly inducible by pro‐inflammatory cytokines and correlates with the severity of major depressive disorder (MDD). MicroRNAs (miRNAs) are involved in gene regulation and the development of neuropsychiatric disorders including MDD. However, the role of miRNAs in targeting IDO1 in the pathophysiology of MDD is still unknown. In this study, we investigated the role of nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Since indoleamine 2,3-dioxygenase 1 (IDO1) is one of the critical mediators in inflammation-mediated depressive-like behaviors ( Jeon et al ., 2017 ) that is activated by toll-like receptor 4 (TLR4)-related ligands and the IFN family ( Hoyo-Becerra et al ., 2014 ; Suento et al ., 2021 ); we conducted the qRT-PCR of IDO1 as well, which showed similar inhibitory effects by hycanthone ( Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since indoleamine 2,3-dioxygenase 1 (IDO1) is one of the critical mediators in inflammation-mediated depressive-like behaviors ( Jeon et al ., 2017 ) that is activated by toll-like receptor 4 (TLR4)-related ligands and the IFN family ( Hoyo-Becerra et al ., 2014 ; Suento et al ., 2021 ); we conducted the qRT-PCR of IDO1 as well, which showed similar inhibitory effects by hycanthone ( Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, although rats in Experiment 2 appeared to avoid the CS+ paired with 10 mg/kg KET (and to a lesser extent, 20 mg/kg KET; Figure 3B), this effect was not significant. Even so, conditioned avoidance is typically associated with a reduction in motor activity (Baidoo et al, 2020; Horman et al, 2018), and stimuli that reduce motor activity tend to increase immobility (Lim et al, 2020; Melanson et al, 2021; Suento et al, 2021). Another study conducted in our laboratory (data not shown) also did not find group differences in avoidance responses to a KET CS+ when a more typical place-conditioning protocol (i.e., 4 drug/CS+ and 4 vehicle/CS− pairings, 30 min each) was utilized (Sticht et al, 2010; Thériault et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Clark et al (2016) has indicated that depression is associated with unexpectedly decreased KP metabolism and cytokine expression in the ventrolateral PFC, which is part of the orbitofrontal cortex region associated with higher emotional function, thus indicating that the brain KP regulation may be region-specific. A recent study has shown that IDO1 expression in mice is upregulated by LPS in the PFC but not in the hippocampus, and microinjection of 1-MT (a potent IDO1 antagonist) or microRNA-874-3p into the PFC downregulates LPS-induced IDO1 expression and ameliorates LPS-induced depression-like behavior, thus revealing that microRNA-874-3p is a novel potential target for the treatment of MDD ( Suento et al, 2020 ). Future research may examine the influence of the gut microbiota on enzymes involved in TRY metabolism along the KP in PFC.…”
Section: Discussionmentioning
confidence: 99%